Meningkatkan Keterampilan Writing of Narrative Text dengan Menggunakan Teaching Materials - Mardiyah Mardiyah; Mustaji Mustaji; Nurmida Catherine Sitompul (Edcomtech, 2019)
Abstrak: Pengajaran menulis Narrative Text untuk siswa SMP tidak mudah karena siswa mengalami kesulitan dalam menyusun kalimat dan mengekspresikan ide dalam ketrampilan menulis. Tujuan penelitian ini menemukan efektifitas pengembangan buku bahan ajar. Pengembangan bahan ajar menggunakan model Borg and Gall dan pendekatan deskriptif kualitatif. Hasil dari reviu kelayakan produk pengembangan yaitu ahli materi (isi) bahasa Inggris sebesar 90%, ahli desain pembelajaran sebesar 95%. Uji coba produk menunjukkan bahwa pengembangan buku bahan ajar ini mampu meningkatkan skor hasil belajar sebesar 45% untuk perlakuan kelas eksperimen. Meskipun, kelas kontrol juga mengalami peningkatan sebesar 40%. Uji coba produk kepada siswa dan guru melalui angket mendapatkan respon yang sangat menyenangkan.Abstract: The teaching of writing Narrative Texts for middle school students is not easy because students have difficulty in composing sentences and expressing ideas in writing skills. The goal of this study is to find the effectiveness of the development of teaching materials. The development of teaching materials is using the Borg and Gall development model and a qualitative descriptive approach. The results of the review of the feasibility of product development as follows the review of English material experts by 90%, review of learning design experts by 95%. The results of this study indicate that the development of teaching materials gives better results than not using teaching materials. There was an increase in the score of learning outcomes by 45%  for the experimental class. Furthemore,The control class also increased by 40%. Product trials for students and teachers through questionnaires received a very good response.